Review of the method of Talmud instruction at Yeshivat Maʿalot - Klein, Menachem (HTS teologiese studies, 2024)
The background of the Maʿlot article is the method of Talmud instruction at the Volozyhn Yeshiva and Yeshivat Maʿalot and investigating the claim of the management of Yeshivat Maʿalot, the head of the yeshiva, and the teaching staff that the yeshiva is a direct continuation of the famed Volozhyn Yeshiva that operated in 19th-century Europe. This claim can be examined from many angles, but the aim of the current article is to focus on one major angle common to the entire yeshiva world over the generations in Israel and abroad, that is, the method of Talmud instruction. The research setting is based on historical sources for teaching Talmud in yeshivot, physical attendance during lessons, interviews with teachers and students, and criticism brought by them and by the authors. The research methods include describing, comparing and criticising the method of instruction at Yeshivat Maʿalot. The research results led to a conclusion regarding the question of whether the above claim is justified. The article fits the scope of the journal because it reveals the teaching methods at Yeshivat Maʿalot.Contribution: The contribution of the article lies in its being the first to offer a critique of the Talmud instruction method employed at Yeshivat Maʿalot, with the aim of rethinking the current instruction method and creating a possible avenue for changing it and adapting it as much as possible to the students’ needs and abilities.